All-Inside, Anatomical Lateral Ankle Stabilization for Revision and Complex Primary Lateral Ankle Stabilization: A Technique Guide. Issue 6 (December 2014) - Prissel, Mark A.; Roukis, Thomas S.
Lateral ankle instability is a common mechanical problem that often requires surgical management when conservative efforts fail. Historically, myriad open surgical approaches have been proposed. Recently, consideration for arthroscopic management of lateral ankle instability has become popular, with promising results. Unfortunately, recurrent inversion ankle injury following lateral ankle stabilization can occur and require revision surgery. To date, arthroscopic management for revision lateral ankle stabilization has not been described. We present a novel arthroscopic technique combining an arthroscopic lateral ankle stabilization kit with a suture anchor ligament augmentation system for revision as well as complex primary lateral ankle stabilization.